Goal-setting strategy and psychological differences in marathon runners compared by gender - Larumbe-Zabala, E.; Garcia-Lluch, J. J.; Agea, E.; Peris-Delcampo, D. (Journal of Human Sport & Exercise, 2019)
Prior to a marathon race, we conducted a cross sectional study with 122 male and 18 female recreational runners at the Expo. Demographic information, running experience, competition level, training details, goal and finishing times, and PODIUM questionnaire on psychological state variables were collected. Motivation, training volume, experience, and relative performance were comparable between male and female marathon runners. However, men were more ambitious and perceived higher self-confidence and fitness, although overestimated their goals (Mdif = -10.4, SD = 16.7] minutes, p < .001). Women perceived higher social support, reported higher anxiety levels, were more accurate in their estimates (Mdif = -0.1, SD = 17.2 minutes, p = .988). Women were also more open than men to consult with (RR = 3.39, 95% CI [1.14, 10.11]) and to remunerate (RR = 1.47, 95% CI [1.18, 1.83]) sport psychologists. Differences in competitiveness might be explained by orientation to competition, personal identity, gender roles and stereotypes, or other physiologic mechanisms. Together with the tendency in men athletes to less likely seek help, been aware of these tendencies could be of help for both sport psychologists and coaches when working with marathon runners